2016
DOI: 10.1093/mnras/stw2288
|View full text |Cite
|
Sign up to set email alerts
|

Reionization in sterile neutrino cosmologies

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 113 publications
11
52
0
Order By: Relevance
“…but there is a sharp increase in the star formation rate in ETHOS haloes for M200 < 4 × 10 9 M . This is consistent with the scenario suggested in Bose et al (2016b) and Lovell et al (2018a), where haloes near the cutoff scale in models with a primordial power spectrum cutoff collapse later relative to CDM but do so more rapidly, thus producing a bright starburst. This is shown explicitly with the blue curve in Fig.…”
Section: Galaxy Propertiessupporting
confidence: 90%
“…but there is a sharp increase in the star formation rate in ETHOS haloes for M200 < 4 × 10 9 M . This is consistent with the scenario suggested in Bose et al (2016b) and Lovell et al (2018a), where haloes near the cutoff scale in models with a primordial power spectrum cutoff collapse later relative to CDM but do so more rapidly, thus producing a bright starburst. This is shown explicitly with the blue curve in Fig.…”
Section: Galaxy Propertiessupporting
confidence: 90%
“…The early structure formation in WDM models has been studied with semi-analytic models and numerical simulations (e.g. Yoshida et al 2003a;O'Shea & Norman 2006;Gao & Theuns 2007;Bose et al 2016;Dayal et al 2017;Lovell et al 2018Lovell et al , 2019. In cosmological hydrodynamic simulations for a WDM cosmology with a particle mass of mχc 2 = 3 keV, Yoshida et al (2003a) found that the formation of star forming clouds is delayed by ∼ 60 Myr, and suppressed in number by about two orders of magnitude, which leads to much less efficient early ionization of the IGM, compared with that in the CDM model calibrated to the initial WMAP data release.…”
Section: Early Structure Formationmentioning
confidence: 99%
“…Previous works have studied the effect of non-CDM models on the 21-cm signal [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Those models typically suppress the matter power spectrum beyond some wavenumber k, delaying the onset of cosmic dawn.…”
Section: Introductionmentioning
confidence: 99%